Papillary carcinoma arising from the pyramidal lobe of the thyroid gland – Two case reports - Theodosios S. Papavramidis; Anna Zisi; Sofia-Eleni Tzorakoleftheraki; Triantafyllia Koletsa; Ioannis Pliakos; Stavros Panidis; George Kotsovolis; Christina Manani; Marina Kita; Antonis Michalopoulos (Journal of Clinical and Translational Endocrinology Case Reports, 2018)
The pyramidal lobe (PL) displays variations and is rarely affected by carcinoma. This manuscript presents two such carcinomas.Case 1: Painful mass in the neck, and swallowing difficulty. Echography showed hypoechoic mass, with Bethesda VI cytology. Total thyroidectomy was performed.Case 2: Prominent mass in the neck for 25 years that enlarged. CT revealed a mass in PL. Total thyroidectomy with prophylactic central compartment was performed, followed by bilateral lymph node dissection.Pathology revealed for the first patient two papillary tumors (pyramidal and right lobe) and for the second a papillary tumor with focal extrathyroideal extension (PL) and multiple papillary microcarcinomas. Central compartment had 3 and lateral 5 lymph nodes infiltrated.Although PL is a non-constant anatomic formation, the oncologic principles followed should be the same as in classic thyroid surgery. The central position of PL may be the reason of bilateral lymph node positivity. Keywords: Pyramidal lobe, Papillary carcinoma, Rare thyroid carcinomas, Total thyroidectomy, Thyroid anatomic variations